All I want for Christmas is a cowboy - Clare, Jessica (Berkley, an imprint of Penguin Random House LLC, 2018)
Snowed in with adorable Cassandra Horn, a woman he rescued, self-proclaimed recluse Eli Pickett finds himself head over heels in love with his unexpected house guest.